The untraditional forms of harmony in the system of training teacher of music (Pedagogy of Higher and Secondary Education, 2007)
This article is devoted to the analisis and the generalized experience of untraditional practice in the assimilation of harmony's course, the introduction of unstandard method in the system of training teacher of music.
Keywords: harmonization; nonconventional harmonization; musical sound (tone); formation of chords; nonconventional formation of chords; chords not a third of structure; thematic harmony; musical warehouse; musical invoice